Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need to find the solution of $$x''-2x'+x=\sum_{n=1}^Ne^{-nt}$$ I was thinking undetermined coefficients. Is there another way?

share|cite|improve this question
up vote 14 down vote accepted

$$x''-2x'+x=\sum_{n=1}^Ne^{-nt}$$ $$e^{-t}(x''-2x'+x)=\sum_{n=1}^Ne^{-(n+1)t}$$ $$(e^{-t}x)''=\sum_{n=1}^Ne^{-(n+1)t}$$ Now define $y(t):=e^{-t}x(t)$ $$y''=\sum_{n=1}^Ne^{-(n+1)t}$$ Now you can integrate twice.

share|cite|improve this answer
Nice trick and the solution seems to be much simpler than the brute force answer from Wolfram Alpha. – gammatester Jul 1 '14 at 11:55
Nice answer!!! Thanks – Luis Valerin Jul 1 '14 at 11:56

The characteristic equation of the homogeneous equation is $$r^2-2r+1=0$$ and has the double root $r=1$ so the homogeneous solution is $$x_h(t)=(at+b)e^t$$ Now we look for a particular solution to the ODE $$x''-2x'+x=e^{-kt}$$ on the form $x_p(t)=\alpha_k e^{-kt}$ and we find $$(k^2+2k+1)\alpha_k=1\iff\alpha_k=(k^2+2k+1)^{-1}$$ and finally by the superposition method the general solution of the given equation is $$x(t)=(at+b)e^t+\sum_{n=1}^N\frac{e^{-nt}}{n^2+2n+1}$$

share|cite|improve this answer

Solution using the method of operators

The equation can be written as
$(D^2 - 2D + 1)x = \sum\limits_{n = 1}^N e^{-nt} \Leftrightarrow\\ (D - 1)^2 x = \sum\limits_{n = 1}^N e^{-nt}$

The auxiliary equation is $(m - 1)^2 = 0 \Rightarrow m = 1, 1$, so the complementary function (solution of the homogeneous equation $(D - 1)^2 x = 0$) is $x_c = (c_1 + c_2 t)e^t$.

To find the particular integral, $x_p$, we use $\dfrac{1}{f(D)}e^{at} = \dfrac{1}{f(a)}e^{at}$ when $f(a) \ne 0$.

Here, $\dfrac{1}{(D - 1)^2}e^{-nt} = \dfrac{1}{(-n - 1)^2}e^{-nt} = \dfrac{1}{(n + 1)^2}e^{-nt}$ (as $n \ne -1)$.

Thus, $x_p = \sum\limits_{n = 1}^N \dfrac{1}{(n + 1)^2}e^{-nt}$.

Therefore, the complete solution is obtained by adding $x_c$ and $x_p$:

$\boxed{x = \sum\limits_{n = 1}^N \dfrac{1}{(n + 1)^2}e^{-nt} + c_1 + c_2 t}$

share|cite|improve this answer

First you can solve $x''-2x'+x=0$. We are looking solution in form $x(t)=e^{\alpha t}$, if you substitute to equation you have $\alpha^2-2\alpha+1=(\alpha-1)^2=0$, $\alpha=1$ is double root, so you have two linear independent solution:$e^{t}$ and $te^{t}$, so general solution is:


Now find special solutions of $x''-2x'+x=e^{-nt}$. It is in form $x(t)=C_ne^{-nt}$, substitute to equation and find $C_n$:

$C_nn^2+2nC_n+1+C_n=1$, so:


Now you know special solution for $x''-2x'+x=\sum_{n=1}^{N}e^{-nt}$, it is: $x(t)=\sum_{n=1}^{N}C_ne^{-nt}$, so finally:


share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.